A novel design protocol for solar-powered carbon capture. (1st December 2021) - Milani, Dia; Luu, Minh Tri; Nelson, Scott; Puxty, Graeme; Abbas, Ali
Highlights: Solar-powered PCC is a sustainable approach to autonomise carbon capture technology. The typical stripper in the PCC is replaced by an innovative solar stripper (So-St). Typical thermal energy storage is replaced by two distinct lean and rich solvent storage. The design protocol synchronizes the process in the absorber, storage, and So-St network. A clear trade-off between solar multiple and solvent storage capacity is realized. Abstract: To solarize the carbon capture industry and move away from the power plant steam cycle, this paper presents a new methodology for solar-powered post-combustion carbon capture (SP-PCC). It comprises a rigorous thermodynamic model for a "solar stripper" (So-St) network design to promote this SP-PCC over the solar-assisted (SA-PCC) counterparts. In this work, the absorber, the So-St network, and the solvent storage are synchronized within a generic design protocol. This design protocol primarily creates an extended design database, and then, applies a set of design filters to shortlist promising designs based on specific physical and/or performance criteria. As a buffering media, solvent storage capacity ( SSC ) is sized to ensure continuous solvent availability at both terminals (absorption–desorption) of the solvent cycle. Three key optimization strategies namely, the absorber stoppage time, synchronized solar multiple ( SM ), and multi-tank mix-match strategy are deployed to reduce the SSC and potentially improve the economic model. It is found that the latter strategy can save up to 49.5% of the SSC requirement compared to the basic two-discrete storage system. Furthermore, by combining these three optimisation strategies, it is found when SM increases by 2.5 folds, the SSC requirement is reduced to only 7.6% of the baseline SSC requirement when SM  = 1. This calculation demonstrates the significant trade-off implications between the SM vs. SSC which can only be enhanced via economic optimizations. Validating this state-of-the-art technology by a rigorous techno-economic and life cycle assessment (LCA) could truly innovate the PCC technology and significantly improve its popularity and sustainability.